Swift 5 for Absolute Beginners : Learn to develop apps for iOS - Kaczmarek, Stefan; Lees, Brad; Bennett, Gary; SpringerLink (Online service); O'Reilly (Firm); Serials Solutions (Berkeley, CA : Apress : Imprint: Apress, 2019)
Stay motivated and overcome obstacles while learning to use Swift Playgrounds and Xcode 10.2 to become a great iOS developer. This book, fully updated for Swift 5, is perfect for those with no programming background, those with some programming experience but no object-oriented experience, or those that have a great idea for an app but haven't programmed since school. Many people have a difficult time believing they can learn to write iOS apps. Swift 5 for Absolute Beginners will show you how to do so. You'll learn Object-Oriented Programming (OOP) and be introduced to User Interface (UI) design following Apple's Human Interface Guidelines (HIG) using storyboards and the Model-View-Controller (MVC) pattern before moving on to write your own iPhone and Apple Watch apps from scratch.
Ch. 1: Becoming a Great iOS Developer -- Ch. 2: Programming Basics -- Ch. 3: It's All About the Data -- Ch. 4: Making Decisions, Program Flow, and App Design -- Ch. 5: Object-Oriented Programming with Swift -- Ch. 6: Learning Swift and Xcode -- Ch. 7: Swift Classes, Objects, and Methods -- Ch. 8: Programming Basics in Swift -- Ch. 9: Comparing Data -- Ch. 10: Creating User Interfaces -- Ch. 11: Storing Information -- Ch. 12: Protocols and Delegates -- Ch. 13: Introducing the Xcode Debugger -- Ch. 14: A Swift iPhone App -- Ch. 15: Apple Watch and WatchKit.
Mode of access: World Wide Web.
Keywords: Apple computer; Programming languages; Computer programming; Electronic books